Analysis of Employment Generation due to Chrysanthemum Cultivation in Mandya District of Karnataka - Mamathalakshmi, N. K. Nagabhushanam, M. S. Nataraju, H. T. Nagaraju, Sowmyashree, (Indian Journal of Extension Education, 2022)
..